(untitled) (European Journal of Health Research, 2015)
Objective: To describe the social support for people with cancer and related quality of life. Methodology: Descriptive correlational cross reach, non-probability sampling, in 132 people diagnosed with cancer who were applied a questionnaire of Social Support in Patients with Cancer and the instrument of Subjective Evaluation of Quality of Life. Results: The average age of adults with cancer was 13.65 ± 50.49 years, female gender predominance (76%). Cancers were breast (40%), cervical (19%) cancer, other cancers (41%) cancer. 65% was with chemotherapy. The average social support was 72.51±21.01 and 66.55±14.64 for the Quality of Life. Social support and quality showed a weak relationship (r=.28**, p=.001), positive and significant. Conclusion: The cancer affects more women, breast cancer out. Relationship between social support and quality of life was found. Most likely due to the fact that adults are strengthened by social support networks (social, family and friends security) and refer good quality of life. Indicating that the higher the social support better quality of life.